Transformasi Pembelajaran Geografi: Implementasi Project Based Learning Berbasis Riset dalam Meningkatkan Kemampuan Critical Thinking - Musyawarah, Rahma; Nasiah, Nasiah; Juanda, Muhammad Faisal; Ningtyas, Novarina Sulsia Ista’in (Jurnal Penelitian Pendidikan Geografi, 2026)
Project Based Learning (PjBL) based on research is important to implement because it integrates research activities into the learning process, enabling students not only to understand theories but also to sharpen critical thinking skills through empirical experiences. This study aims to: 1) describe the design of research-based PjBL learning; and 2) analyze its effect on improving the critical thinking skills of Geography Education students at Universitas Negeri Makassar. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest format. The sample consisted of two classes, namely a control class that learned through conventional methods and an experimental class that applied research-based PjBL, with 35 students in each class. The findings show that: 1) the design of research-based PjBL follows the main stages of PjBL, namely: a) problem orientation, b) formulation of research questions, c) project planning, d) research implementation, e) product development, f) presentation and publication, and g) reflection and evaluation. 2) The t-test results indicate Sig. (2-tailed) = 0.000 < 0.05. Thus, H0 is rejected and H1 is accepted, meaning that students who learned through research-based PjBL achieved higher critical thinking scores than those who learned through conventional methods. Furthermore, the Mean Difference = -6.28571, indicating that the average critical thinking score of students in the experimental class was approximately 6.28 points higher than that of the control class.